DEVELOPING READING COMPREHENSION MATERIALS BASED ON OUTCOME BASED EDUCATION (OBE) FOR ELEVENTH GRADE STUDENTS AT SMA AL-WASHLIYAH 12 SEI RAMPAH IN ACADEMIC YEAR 2023-2024 - Dara, Febri Risma; Arfanti, Yulia; Risnawaty, Risnawaty; Asnawi, Asnawi (PHILOLOGY Journal of English Language and Literature, 2025)
Reading comprehension is crucial for learning English, and teachers need to improve their teaching methods. Outcome-Based Education focuses on essential skills for students to succeed, requiring creativity in delivering learning materials using interesting media and methods. The research focused on the development, validation, and effectiveness of reading comprehension materials using Outcome-Based Education (OBE) for Grade Eleventh students at SMA AL WASHLIYAH 12 SEI RAMPAH. The study involved 15 students and used various techniques, including study literacy, interviews, observation, group discussion, and documentation. The research using quantitative descriptive techniques that described the application of learning media. The results showed successful development with an average increase of 9.13% and a passing rate of 86.66%. The method was also proven valid with an average score of 4.1 and effective with an Ngain percentage score of 81.94%.